Internalization of Principles of Islamic Supervision For Minimize Fraud in Government - Asmin Asmin; Achmad Abubakar; Hasyim Haddade; Abdul Azis (Economos : Jurnal Ekonomi dan Bisnis, 2022)
The emergence of fraud is generally a combination of motivation and opportunity. The aim of this research is to reveal the essence of Islamic supervision in order to minimize immoral acts such as fraud that often occur in government agencies. This study uses a qualitative descriptive research design. The author tries to provide a more progressive picture of the Islamic supervisory system as a preventive step in minimizing acts of fraud within the scope of the organization. The data source used by the author is from the results of previous research and of course the theories that support writing related to Islamic supervision so that conclusions are drawn from this paper. The results of the study showed that fraud is foul caused by moral weakness of person, so an alternative is needed to strengthen these morals. By adopting Islamic supervision, it is very effective for every element in government agencies in minimizing acts of fraud. Islam believes that supervision can come from within oneself with the assumption that Allah SWT is All-Knowing of everything that is done by humans so that an attitude of caution will emerge in doing work, besides that Islam also believes that supervision must be integrated into the supervisory system itself to be present as a control over wrong actions and justify the right.